2011
DOI: 10.1088/1742-6596/272/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of isotactic polypropylene from mesomorphic phase: a constant heating rate study

Abstract: Abstract.We have studied crystallization behaviour of isotactic polypropylene (iPP) from mesomorphic phase in structural point of view. Time-resolved wide-angle X-ray diffraction (WAXD) measurements during a heating process have been performed using a synchrotron radiation (SR) X-ray beam line at SPring-8, Japan. The heating process was so programmed to reproduce a thermal trace of differential scanning calorimetry (DSC) with a constant heating rate (10 °C/min) in order to compare the structural change with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…However, in our case, crystallization hardly occurs from the amorphous region, but occurs mainly from the mesomorphic phase. A reasonable explanation can be found in the most recent work of Asakawa et al, 30 in which it is verified that compared with the transitions of mesomorphic to amorphous phases and amorphous to crystalline phases, the energy level for the transition of mesomorphic to crystalline phases is much lower. For the iPP samples prequenched at the rates of 1000 and 686 °C/s, the temperatures at which the α-monoclinic crystals are completely melted are 162.5 and 158.3 °C, respectively.…”
Section: Resultssupporting
confidence: 67%
“…However, in our case, crystallization hardly occurs from the amorphous region, but occurs mainly from the mesomorphic phase. A reasonable explanation can be found in the most recent work of Asakawa et al, 30 in which it is verified that compared with the transitions of mesomorphic to amorphous phases and amorphous to crystalline phases, the energy level for the transition of mesomorphic to crystalline phases is much lower. For the iPP samples prequenched at the rates of 1000 and 686 °C/s, the temperatures at which the α-monoclinic crystals are completely melted are 162.5 and 158.3 °C, respectively.…”
Section: Resultssupporting
confidence: 67%
“…8,[10][11][12][13][14][15] Additionally, the crystallization of iPP via the mesophase has been extensively studied in the literature. 7,[16][17][18][19][20][21] However, the ongoing process of mesophase formation has been a black box for many years, and in situ observation of the formation process, which occurs in a very short period of time, has been challenging.…”
Section: Introductionmentioning
confidence: 99%
“…7,24 Thus, the formation of the mesophase of iPP is one of the solidification processes, which accompanies an exotherm (latent heat) sufficient to stabilize the mesophase at room temperature (above the T g ). 21 The understanding of the formation process of the mesophase iPP has progressed significantly as a result of thermal analysis.…”
Section: Introductionmentioning
confidence: 99%
“…2 a is the Wide‐Angle X‐ray Diffraction (WXRD) spectra of the MBPP fabrics annealed at 60°C. It is shown that there are two strong wide peaks, wherein 2 θ values are 15.0° and 21.3°, respectively, which are the characteristic peaks of mesomorphic crystallite [44]. No obvious change of WXRD spectra is observed when the samples are annealed for more time, although the sketch of other peaks appears due to a glass transition‐like behaviour resulting from the chain reorganisation of the interfacial region of the mesophase [45].…”
Section: Experiments Resultsmentioning
confidence: 99%